Ethics : contemporary challenges in health and social care - Leathard, Audrey; Goodinson-McLaren, Susan (Policy Press, 2007)
While ethics has been addressed in the health care literature, relatively little attention has been paid to the subject in the field of social care. This book redresses the balance by examining theory, research, policy and practice in both fields. The importance of this approach is reflected in the growing emphasis on ethical issues in research and practice and, in Britain, on government policy aimed at improving partnership working across the two sectors.